Amniotic band syndrome - Suárez Camargo, Mónica Natalia (2024)
Amniotic banding sequence is a congenital disorder caused by early rupture ofthe amnion resulting in the development of amniotic bands that become attachedor entangled in the fetus and generate a spectrum of fetal anomalies (disruption,deformity and/or malformation). Its incidence varies from 1 in 1,200 to 1 in 15,000live births and would be responsible for 1/70 fetal deaths. The prognosis dependson the extent of the defects, which can range from minor anomalies to lethal onessuch as umbilical cord constriction, causing fetal death or spontaneous abortions.We present the case of a patient with prenatal diagnosis of amniotic bands withsevere deformities - asymmetry of the skull, exposure of brain tissue, amelia of theupper extremity, malposition of the lower extremities - emphasizing the importanceof early diagnosis of this pathology in order to define timely procedures.